(untitled) (Plant Bulletin, 2024)
Soil salinity affects nearly one billion hectares of land globally, posing a serious challenge to plant growth and agricultural productivity. To enhance crop performance and restore saline soils, integrated agronomic methods, sustainable management practices, and soil remediation strategies are essential. A study was carried out in a completely randomized design (CRD) with the objective to determine the effect of a combination of bentonite, compost, and gypsum on the yield of wheat, in addition to the rehabilitation of salinized soil. Overall, five treatments with three replications, viz., T0 (control), T1 (recommended N, P, and K fertilizer), T2 (94% compost + 1% gypsum + 5% bentonite), T3 (75% compost + 3% gypsum + 5% bentonite), and T4 (50% compost + 5% gypsum + 5% bentonite), were used. In comparison to the control and NPK treatments, the T4 showed the greatest improvement in wheat crop growth metrics, including plant biomass (56%), number of leaves (26%), plant height (61%), leaf length (48%), leaf width (21%), root length (47%), and shoot length (58%). Meanwhile, T3 increased spike length (82%), spikelets (46%), and 1000-grain weight (82%). Under saline circumstances, compost containing gypsum and bentonite significantly enhanced soil physiochemical characteristics, crop production, and chlorophyll content.